Penjaminan Hak-Hak Istri dan Anak Pasca Perceraian dalam Hukum Keluarga Islam: Studi Komparatif Antara Indonesia dan Malaysia - Dwi Pamudi, Toto (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2024)
This study aims to analyze the safeguarding of wives' and children's rights after divorce under Islamic family law in Indonesia and Malaysia, as well as to compare its implementation in both countries. The study employs a qualitative approach using a comparative study method to analyze regulations and practices related to post-divorce rights, including iddah maintenance, division of joint property, child custody, and rights over the dowry. Primary data were obtained from literature such as journals, books, and relevant online sources. The findings reveal that although Islamic family law principles are similar in Indonesia and Malaysia, the implementation of these rights differs. In Indonesia, law enforcement is often hindered by social and cultural factors, whereas Malaysia adopts more structured procedures despite challenges faced by Syariah courts in accommodating the best interests of the child. Factors such as differences in legal systems, the role of religious courts, and socio-cultural aspects influence the execution of post-divorce rights for wives and children in both countries. This research provides a deeper understanding of the similarities and differences in safeguarding these rights and offers recommendations for improving the implementation of Islamic family law in Indonesia and Malaysia.